SECURITY CAPABILITY ANALYSIS OF COGNITIVE RADIO NETWORK WITH SECONDARY USER CAPABLE OF JAMMING AND SELF-POWERING - Dan, Ngoc Pham Thi; Van, Khuong Ho; Ngoc, Hanh Dang; Dac, Thiem Do; Huu, Phong Nguyen; Que, Son Vo; Ngoc, Son Pham; Pham, Lien Hong (Journal of Computer Science and Cybernetics, 2020)
This paper investigates a cognitive radio network where a secondary sender assists a primarytransmitter in relaying primary information to a primary receiver and also transmits its own information toa secondary recipient. This sender is capable of jamming to protect secondary and/or primary informationagainst an eavesdropper and self-powering by harvesting radio frequency energy of primary signals.Security capability of both secondary and primary networks are analyzed in terms of secrecy outageprobability. Numerous results corroborate the proposed analysis which serves as a design guidelineto quickly assess and optimize security performance. More importantly, security capability trade-offbetween secondary and primary networks can be totally controlled with appropriate selection of systemparameters.